Data Security System login With MD5 Algorithms in Applications deskresy.com - Rahmat Ferdiansyah; Paska Marto Hasugian (Journal of Computer Networks, Architecture and High Performance Computing, 2020)
Cryptography is a technique of data security by processing the data (plaintext) using an encryption method so that the the data can not be read directly, especially by unauthorized parties. Confidential Data and information need to get serious attention considering the value of information contained in it so that procedures are needed to hide the messages stored Therein. Data security Becomes very important at this time, Because for every decision or policy making must be based on the data. Md5 is a substitute for MD4, MD5 is one of the most Widely used one-way hash functions, MD5 processes the input into blocks of 512 bits, the output of md5 is 128 bits and has a fixed length. MD5 algorithm is Widely used for various purposes in making security in applications, it is Often used to help login validation on the use of passwords stored in the database system